Stable microencapsulated phase change materials with ultrahigh payload for efficient cooling of mobile electronic devices. (1st November 2020) - Zhu, Xiangyu; Li, Xiang; Shen, Jiajun; Wang, Bijia; Mao, Zhiping; Xu, Hong; Feng, Xueling; Sui, Xiaofeng
Graphical abstract: Highlights: Regenerated nanochitin as a super-efficient Pickering stabilizer to microencapsulate paraffin wax. Unprecedented payload (91.3%) of PCMs and high heat capacity (230 J/g) achieved. Good compositability and cyclability due to favorable mechanical properties. Suitable mechanical strength and thermal stability to be applied in mobile phones. Abstract: Microencapsulated phase change materials (microPCMs) of core–shell structure with high payload were fabricated via Pickering emulsion stabilized by regenerated nanochitin (RCh) and its subsequent interfacial polymerization with isocyanate. Size and shell thickness of the microPCMs were tunable by varying concentration of RCh and isocyanate. Due to the super-efficient Pickering stabilizing property of RCh, microPCMs with payload as high as 91.3% and phase-transition enthalpy of 230 J/g were obtained, which demonstrated high thermal durability in retaining 99.5% of their phase-transition enthalpy after 100 heating and cooling scans. Silicone rubber (SR)/microPCMs sheets were further prepared and shown to effectively delay temperature rise in a mobile phone caused by transient surges in processor usage.